2017
DOI: 10.1021/acsami.7b10904
|View full text |Cite
|
Sign up to set email alerts
|

Significance of a Noble Metal Nanolayer on the UV and Visible Light Photocatalytic Activity of Anatase TiO2 Thin Films Grown from a Scalable PECVD/PVD Approach

Abstract: UV and visible light photocatalytic composite Pt and Au-TiO coatings have been deposited on silicon and glass substrates at low temperature using a hybrid ECWR-PECVD/MS-PVD process. Methylene blue, stearic acid, and sulfamethoxazole were used as dye, organic, and antibiotic model pollutants, respectively, to demonstrate the efficiency of these nanocomposite coatings for water decontamination or self-cleaning surfaces applications. Raman investigations revealed the formation of anatase polymorph of TiO in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 63 publications
4
19
0
Order By: Relevance
“…HMDSO flow), the positions of the Ti 2p 1/2 and Ti 2p 3/2 peaks, observed at 464.5 eV and 458.8 eV (Fig. 4b ), respectively, is characteristic of TiO 2 bondings This value is very close to that of pure TiO 2 generally reported 8 , 15 , 19 , 20 , indicating that Ti is predominantly involved in Ti-O-Ti bonding. Nevertheless, Ti-O-Si bonding can not be excluded as the peak shows a significant full width at half maximum (FWHM) of 1.5 eV.…”
Section: Resultssupporting
confidence: 59%
“…HMDSO flow), the positions of the Ti 2p 1/2 and Ti 2p 3/2 peaks, observed at 464.5 eV and 458.8 eV (Fig. 4b ), respectively, is characteristic of TiO 2 bondings This value is very close to that of pure TiO 2 generally reported 8 , 15 , 19 , 20 , indicating that Ti is predominantly involved in Ti-O-Ti bonding. Nevertheless, Ti-O-Si bonding can not be excluded as the peak shows a significant full width at half maximum (FWHM) of 1.5 eV.…”
Section: Resultssupporting
confidence: 59%
“…Although well-organized titania nanostructures might be easily obtained by a convenient hydrothermal method, such as nanowires (1D), nanotubes (1D), and faceted NPs (0D), other methods are used for the preparation of 2D titania nanostructures since titania films are usually deposited on some supports, such as glass, polyvinyl chloride, and quartz. Therefore, chemical vapor deposition (CVD) [152], plasma-enhanced chemical vapor deposition (PECVD) [153], dc-sputtering [154], anodization (exemplary shown in Figure 11 as "mesopores") [155] and successive-ionic-layeradsorption-and-reaction (SILAR) [156] methods have been proposed for the preparation of 2D titania photocatalysts. However, hydrothermal methods have been also used for the preparation of titania nanoplates (shown in Figure 13) for application as sensors to detect toxic gases [157].…”
Section: Two-dimensional Titaniamentioning
confidence: 99%
“…Muthuraja et al [13] conducted experiments on PECVD-Chromium diamonds like carbon (Cr-DLC) coated nozzle needle surface and revealed that it is to wear protective. Baba et al [14] investigated the PECVD-PVD hybrid nanocoatings of TiO 2 on the cutting tool and revealed that the deposition of surface coating is suitable for only self-cleaning surfaces. Asha et al [15] explain that when HCHCr alloy steel machined by multilayer coated carbide inserts the tool life is increased.…”
Section: Introductionmentioning
confidence: 99%